Resisting Xenophobia: Transatlantic Mobility and Aleksandar Hemon’s Immigrant Autobiography The Book of My Lives - Elvira Bolanca-Lowman (Current Objectives of Postgraduate American Studies)
The article examines the significance of xenophobic language used in the current portrayal of migration in mainstream media and its potential to determine Western – i.e. especially U.S. American and European – understandings of the migration debate. By critically observing how politically diverse media outlets essentialize the identity of migrants, the article attempts to expose the dangers inherent in the emerging xenophobic anti-immigration rhetoric. The focus on Aleksandar Hemon’s personal account of displacement and the subsequent difficulties and opportunities that arise from his life in diaspora serve to humanize the migrant self. In this context, special attention will be paid to Hemon’s ability to both transgress national ideas of belonging and reconstruct a self that is at home in Sarajevo as well as in Chicago. The selected sections from Hemon’s autobiographical narration will be put into a dialogue with the abstract images of an immigrant deeply rooted in xenophobic discourses.